Simulation and experimental validation: waste cooking oil transesterification using rushton and elephant ear impellers - Mohiuddin, A. K. M.; Adeyemi, Nabeel A.; Mirghani, Mohamed Elwathig Saeed; Aibinu, Abiodun Musa; Aziz, Rashid A.; Firmansyah, F.; Anbese, Yohannes Tamirat (2011)
The performance of two impellers (Rushton and Elephant ear) for waste cooking oil (WCO) transesterification were experimentally and numerically evaluated inside a unbaffled and baffled stirred tank reactor (STR). Three parameters (impeller bottom distance (C), speed, (N) and temperature) were investigated for fatty acid methyl esters (FAME) yield using a Taguchi orthogonal array (OA) experimental design. The mixing study is based on the - and large eddy simulation (LES) turbulent model using a multiple reference frame (MRF) approach and the result was validated by particle image velocimetry (PIV) measurement. Overall flow structure in the baffled in STR was isotropic at C = 20, 25 and 30 mm for Rushton and to a lesser extent at the STR centre in the unbaffled STR. Mean radial velocities of the Elephant ear impeller was about 25-30% of the Rushton impeller for 600 rpm and 85-90% in baffled STR at C = 30 mm in the unbaffled STR. CFD results of - and LES results were qualitatively similar at mid-impeller plane than for the other parts of the STR. However, none of the model could capture the vortex trailing encountered with Rushton impeller. Experimental mixing time, a function of FAME yield and liquid velocities were found to be dependent on stirrer speeds, impeller bottom distance and bulk flow pattern. The study demonstrated the effect of different impeller types used in the laboratory on FAME yield and attributed to flow characteristics. This model is being used to evaluate other conditions of the reactions.